Analisis Model Budidaya Ikan Air Tawar Berdominansi Ikan Gurame (Osphronemus Gouramy) di Desa Sukawening, Bogor, Jawa Barat - Lia Sutiani; Yannefri Bachtiar; Amiruddin Saleh (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Aquaculture is a fishery activity that produces aquatic biota (organism) in a controlled environment that aims to benefit. Freshwater fish is one of the economically valuable aquaculture commodities. Bogor Regency is one area that has developed freshwater aquaculture. One of the villages in Bogor Regency which has tried to breed freshwater fish is Sukawening Village. The purpose of this activity is to observe and analyze the models or techniques of freshwater fish farming applied, as well as the potential for development which is located in Sukawening Village, Dramaga District, Bogor Regency, West Java Province through the SUIJI-SLP program. The method applied is a field study through observation and interviews supplemented with secondary data using literature study. The results of these observations and analyzes indicate that the model of freshwater fish farming applied in Sukawening Village is still relatively simple and on a small scale. This condition is due to lack of supporting facilities without capital and lack of in-depth knowledge related to freshwater fish farming. Keywords: aquaculture, Sukawening Village, freshwater fish